Socioeconomic Determinants of Profitability in Snail Marketing: A Gender-Based Perspective in Delta State - Ezekiel Ukwama; Theophilus Miebi Gbigbi (CV Projurnal Mitra Publikasi, 2025)
This study examines profitability dynamics in snail marketing, emphasizing the factors that shape success within the industry. Key variables influencing profitability include education, marketing experience, quantity sold, selling price, and gender-income interactions, with notable gender differences highlighted by t-test analysis. Results reveal that female marketers not only participate actively but achieve higher profits than male counterparts, suggesting that targeted gender-specific interventions could amplify their success and promote equity in the agricultural sector. Market awareness and channel utilization play crucial roles, with 42.5% of respondents recognizing snail market potential and 40.4% primarily selling in local markets. Additionally, 45% of marketer’s source snails from farms, underscoring the need to strengthen local markets and supply chains to enhance profitability and sustainability in snail marketing. These insights offer a foundation for targeted strategies to support and expand this promising niche within rural economies.